Narrativ medicin som utforskande praktik - Holmgren, Daniel; Vallo Hult, Helena (Socialmedicinsk tidskrift, 2024)
The Swedish Association for Narrative Medicine organizes workshops and film festivals to provide healthcare professionals and others with opportunities to meet and discuss humanistic values within healthcare. An evaluation of these meeting places showed that the participants were personally affected by what they experienced and that the stories told were sometimes so vivid that they resembled real meetings. The significance of the participants’ experiences for clinical everyday life may not be immediately obvious. However, we suggest that the carer role narrative medicine tries to reach can be seen as a ”living instrument” that requires calibration and that the meeting places serve as a method for calibrating the carer role. Thus, a way to open up to not only an explanation but also an understanding of the person behind the disease.